Effect of Chitosan-PMAA-Nutrients Slow-release Fertilizer on Germination of Falcataria moluccana (Miq.) Barneby & J. W. Grimes - Hilmi Naufal Madani; Nurheni Wijayanto; Adisti Permatasari Putri Hartoyo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Slow-release fertilizer (SRF) with chitosan (CS) coating as a supply of plant nutrients is an alternative to the efficient use of conventional chemical fertilizers and reduces environmental pollution. However, its potential in woody plants is limited. This study aimed to analyze the effect of SRF on Falcataria moluccana germination and SRF phosphorus release rate. This study used SRF from polymerizing CS with methacrylic acid (MAA) to trap nutrients (CS-PMAA-nutrients SRF). The seeds of F. moluccana were germinated at six concentrations SRF: without fertilizer (F0), SRF CS dose 0.5% weight 0.03 g (F1), SRF CS 0.5% 0.01 g (F2), SRF CS 0.7% 0.03 g (F3), SRF CS 0.7% 0.01 g (F4), and conventional fertilizer (F5) for 21 days. SRF can increase the germination of F. moluccana. F4 increased normal sprout (10%) and germination power (16%) of F. moluccana. Furthermore, SRF with a concentration of 0.01 g produced a higher germination value than a concentration of 0.03 g. The release rate of SRF’s nutrients was slower (91.80% phosphorus) than conventional fertilizers. SRF application can reduce nutrients lost and increase the efficiency of nutrient absorption. Hence, it can improve F. moluccana growth.